(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Chana (Cicer arietinum) is a common food plant worldwide. This crop is well documented as a medicinal plant in traditional medicine systems. The antidiabetic activity of Chana seed extracts were examined in vitro and compared with the activity in germinated seed extracts. The results indicated the enhancement of activity upon germination. The dry seeds (C1) showed minimum activity in in-vitro α-glucosidase inhibition compared to the germinated sprouts of different intervals (C2, C3 and C4). In vitro α—amylase inhibition activity also proved to enhanced upon germination. The germination therefore is said to boost up the antidiabetic activity in Chana seeds.